2007
DOI: 10.1158/1078-0432.ccr-06-1568
|View full text |Cite
|
Sign up to set email alerts
|

High Human Papillomavirus Oncogene mRNA Expression and Not Viral DNA Load Is Associated with Poor Prognosis in Cervical Cancer Patients

Abstract: Purpose: Cervical cancer is now known to be caused by infection with an oncogenic type of the human papillomavirus (HPV). However, little is known about the continued role of HPV once cancer has been established. Here, we describe the quantitative relation between HPV DNA copy number and mRNA expression of the viral oncogenes (E6 and E7) and the prognostic value of both measures in cervical cancer patients. Experimental Design: We studied the number of viral DNA copies and the level of HPV E6/E7 mRNA expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
3
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 30 publications
5
72
3
2
Order By: Relevance
“…27 In addition, E6/E7 mRNAs for 5 HR-HPV (HPV16, 18, 31, 33 and 45) were analyzed in all the HPV-DNA-positive samples by real-time multiplex NASBA NucliSENS EasyQ HPV kit (bioMerieux SA, Marcy L'Etoile, France) as described in Ref. 8.…”
Section: Hpv E6/e7 Transcript Detectionmentioning
confidence: 99%
“…27 In addition, E6/E7 mRNAs for 5 HR-HPV (HPV16, 18, 31, 33 and 45) were analyzed in all the HPV-DNA-positive samples by real-time multiplex NASBA NucliSENS EasyQ HPV kit (bioMerieux SA, Marcy L'Etoile, France) as described in Ref. 8.…”
Section: Hpv E6/e7 Transcript Detectionmentioning
confidence: 99%
“…Low HPV viral load by Hybrid Capture II test in cervical specimens from patients with cervical carcinoma treated by radiation therapy was an independent prognostic predictor of poor clinical outcome (Datta et al, 2006;Kim et al, 2009), although the clinical significance of HPV viral load was not confirmed in other studies (De Boer et al, 2007;Kim et al, 2008;Kang et al, 2011). In the study by de Boer et al (De Boer et al, 2007), a high expression of E6/E7 mRNA of HPV16 or HPV18 was a poor prognostic predictor in surgically-treated patients with cervical carcinoma of non-NECA type, whereas the DNA viral load was not. It may be uncertain whether the variation in sample types or study methods would affect the assessment of the clinical significance of HPV viral load in cervical carcinoma.…”
Section: Discussionmentioning
confidence: 89%
“…In nasal NK/Tcell lymphoma, a low viral load of Epstein-Barr virus detected in formalin-fixed paraffin-embedded tissue was reported to be associated with better overall survival of the patients, compared to the high viral load (Hsieh et al, 2007). The prognostic value of HPV viral load has been evaluated in studies on HPV-associated cancers such as tonsillar squamous cell carcinoma and cervical carcinoma (Mellin et al, 2002;Datta et al, 2006;de Boer et al, 2007;Cohen et al, 2008;Kim et al, 2008Kim et al, : 2009Gnanamony et al, 2009;Kang et al, 2011). The studies on HPV16 DNA viral load detected in tissue samples (fresh frozen or paraffin-embedded) of tonsillar carcinoma demonstrated a significant association between low viral load and adverse prognosis (Mellin et al, 2002;Cohen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations